2015
DOI: 10.1007/s00330-015-3672-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple procedures and cumulative individual radiation exposure in interventional cardiology: A long-term retrospective study

Abstract: • A cohort study of 147 patients showed 27.6% low appropriateness procedures. • Potentially avoidable radiation exposure cumulated up to about 186 mSv for single patients. • Predisposing factors were prior bypass surgery and first treatment in a tertiary centre. • 7.5% of the patients received 58% of the potentially avoidable radiation exposure. • The benefits of guideline adherence in decreasing patient radiation exposure are exemplified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Overuse of CC is not only risky for patients in the short term but is potentially associated with avoidable radiation exposure. A German study on multiple procedures and cumulative individual radiation exposure in interventional cardiology calculated exposures of up to 185 mSV in individual patients 7. Also, it is assumed that at least US$158 billion are spent on unnecessary treatments,8 that is, 30% of healthcare expenditures in the USA are preventable 9.…”
Section: Introductionmentioning
confidence: 99%
“…Overuse of CC is not only risky for patients in the short term but is potentially associated with avoidable radiation exposure. A German study on multiple procedures and cumulative individual radiation exposure in interventional cardiology calculated exposures of up to 185 mSV in individual patients 7. Also, it is assumed that at least US$158 billion are spent on unnecessary treatments,8 that is, 30% of healthcare expenditures in the USA are preventable 9.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study of 147 individual patient careers spanning back up to 28 years, we showed that patients with more than 10 CCs in a lifetime had a higher rate of procedures classified as ‘low appropriateness’ (72%) compared with those with fewer procedures (20% in 1–5 procedures and 52% in 6–9 procedures). 12 …”
Section: Introductionmentioning
confidence: 99%